2019
DOI: 10.1371/journal.pone.0215156
|View full text |Cite
|
Sign up to set email alerts
|

The match-play sprint performance of elite senior hurlers during competitive games

Abstract: The typical sprint profile in elite hurling has yet to be established. The purpose of this study was to investigate the sprinting demands of elite hurling competition and characterize the sprinting patterns of different playing positions. GPS (10-Hz, STATSports Viper) were used to collect data from 51 hurlers during 18 games. The total sprint (≥22 km·h -1 ) distance (TSD), the number of sprints (NOS) classified as length (<20 m, ≥20 m) and relative speed thresholds (<80%, 80–90%, >90%), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
45
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(47 citation statements)
references
References 35 publications
2
45
0
Order By: Relevance
“…Research in team sport has provided valuable information about the movement demands of elite players during match-play describing the different locomotion intensities ranging from low to high speeds [13]. The emergence of player tracking technology has facilitated the capability to assess the match-play locomotion ranging from walking to sprinting as reported in soccer, rugby and Australian football [2,46]. Consequently, global positioning system (GPS) technology has been used to quantify the positional profile and temporal changes during match-play [2,46].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Research in team sport has provided valuable information about the movement demands of elite players during match-play describing the different locomotion intensities ranging from low to high speeds [13]. The emergence of player tracking technology has facilitated the capability to assess the match-play locomotion ranging from walking to sprinting as reported in soccer, rugby and Australian football [2,46]. Consequently, global positioning system (GPS) technology has been used to quantify the positional profile and temporal changes during match-play [2,46].…”
Section: Introductionmentioning
confidence: 99%
“…The emergence of player tracking technology has facilitated the capability to assess the match-play locomotion ranging from walking to sprinting as reported in soccer, rugby and Australian football [2,46]. Consequently, global positioning system (GPS) technology has been used to quantify the positional profile and temporal changes during match-play [2,46]. These studies have focused on presenting distances covered using fixed absolute speed-based thresholds (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…RSA has previously been reported as an important physical quality with regard to hurling match-play performance [ 4 ]. RSA has been identified as a determining factor in goal scoring situations during soccer match-play, with 45% of all analysed goals scored preceded by a bout of RSA [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was previously identified that position directly influences the work-rate profiles observed during hurling match-play with midfielders (MF), completing significantly more TD and HSD than other positional lines of play [full backs (FB), half backs (HB), half forwards (HF), and full forwards (FF)] [ 2 ]. Interestingly, high-speed work rate was shown to decrease throughout match-play, most notably at the latter stages of each half [ 2 , 4 ], with a distinctive positional trend also present. The largest decrement in HSD was observed in half forwards (27%) followed by half backs (24%), full forwards (23%), midfielders (22%), and full backs (13%).…”
Section: Introductionmentioning
confidence: 99%